2000
DOI: 10.1046/j.1365-3091.2000.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Miocene silcretes in argillaceous playa deposits, Madrid Basin, Spain: petrological and geochemical features

Abstract: Four regressive sequences are present in the opaline rocks and related deposits of the Miocene Intermediate Unit of the Madrid Basin. The sequences consist of silty mudstones and argillaceous opals, separated by transitional facies. The silty mudstone consists mainly of dioctahedral smectites, whereas the argillaceous opal is principally opal‐CT and variable amounts of sepiolite. In the transitional facies, lamina of dioctahedral smectite co‐exist with neoformed opal‐CT and sepiolite. Petrological and geochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The inferred rapid precipitation of silica and the predominance of opal rather than quartz in Miocene stromatolites indicate that the opal formation was possibly encouraged by the evaporation processes. The evaporation mechanisms provide the high concentrations of silica in the water and the rapidity required for the precipitation of opal (Bustillo & Bustillo, 2000). Papers by Wopfner (1978) and Ambrose & Flint (1981) suggested that shorelines of regressive lakes were the preferred sites for silica precipitation owing to the high evaporation rates.…”
Section: Discussion and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…The inferred rapid precipitation of silica and the predominance of opal rather than quartz in Miocene stromatolites indicate that the opal formation was possibly encouraged by the evaporation processes. The evaporation mechanisms provide the high concentrations of silica in the water and the rapidity required for the precipitation of opal (Bustillo & Bustillo, 2000). Papers by Wopfner (1978) and Ambrose & Flint (1981) suggested that shorelines of regressive lakes were the preferred sites for silica precipitation owing to the high evaporation rates.…”
Section: Discussion and Interpretationmentioning
confidence: 99%
“…This interpretation is based mainly on the transitional relationships between dolomite and silica beds, the typical pustular mat morphologies preserved in some of the silica facies, the relatively light 18 O values for associated dolomite, and the higher density of bioturbation traces in silica than in dolomite beds. Bioturbation tubes create further organic micro‐environments suitable for silica nucleation, as described by several authors (Gardner & Hendry, 1995; Bustillo & Bustillo, 2000). The drop in water level in the lake is interpreted as possibly having led to a rapid silicification of microbial mats developed in the marginal fringes which prevented their degradation and the subsequent dolomite precipitation.…”
Section: Discussion and Interpretationmentioning
confidence: 99%
“…Preservation of the morphology of the buttes was strongly conditioned by the occurrence of chert horizons at several levels within the upper portion of the Intermediate Unit of the Miocene. These chert horizons formed mainly by early diagenetic replacement of calcareous and/or mudstone deposits (Bustillo & Bustillo, ; Bustillo & Alonso‐Zarza, ).…”
Section: Geological Settingmentioning
confidence: 99%
“…The silcretes are very common, and many petrological types have been described in relation to their mineralogical composition, textures, and host rocks (Bustillo 1976). Lacustrine-palustrine limestones, calcretes, dolocretes, gypsum, and Mg-clay deposits are the host rocks of these groundwater or vadose silcretes (Bustillo 1984;Bustillo and Bustillo 1987;Bustillo and Bustillo 2000). At the south of the Madrid basin, near the villages of Cabañas and Yunclillos (Fig.…”
Section: Introductionmentioning
confidence: 99%